Assessment of atrial electromechanical delay and P wave dispersion in patients with chronic obstructive pulmonary disease - Murat Cimci; Sermin Borekci; Burcak Kilickiran Avci; Ergi Hysi; Hurrem Gul Ongen; Bilgehan Karadag; Ozge Ozden Tok; Eser Durmaz; Hakan Karpuz (Türk Kardiyoloji Derneği Arşivi, 2020)
Objective: Chronic obstructive pulmonary disease (COPD) is associated with atrial fibrillation (AF) and reduced forced expiratory volume (FEV1) is an independent predictor for new onset AF. The aims of this study were (1) to analyze the atrial electromechanical delay (AEMD) and P wave dispersion which are two predictors of AF development in patients with COPD and without any cardiovascular disease, and (2) to assess the relationship of those with pulmonary functions as quantified by FEV1 measurements. Methods: The study included 41 patients with COPD (33 male; mean age: 51 years) and 32 healthy controls. P wave dispersion was calculated as the difference between the maximum and minimum P wave duration in a 12-lead surface electrocardiography (ECG) recording. AEMD, defined as the time interval from the P wave onset on the ECG to the initiation of the late diastolic (Am) wave using a tissue Doppler examination, was measured from the lateral mitral annulus (LAEMD), septal annulus (SAEMD), and tricuspid lateral annulus (TAEMD). Results: P wave dispersion was significantly longer in the COPD group than those in the controls (76+-19 ms vs. 45+-10 ms; p<0.001). All of the AEMD measurements demonstrated significant prolongation in patients with COPD (LAEMD: 74+-9 ms vs. 64+-11 ms; SAEMD: 66+-10 ms vs. 57+-12 ms; and TAEMD: 65+-9 ms vs. 46+-7 ms; p<0.001 for all). The only correlation with FEV1 was observed in the TAEMD values of the COPD group (rs: -401; p<0.009). Conclusion: Both P wave dispersion and AEMD parameters were significantly longer in COPD patients without any established structural or functional cardiac abnormalities, indicating an increased tendency for AF development, beginning from the initial stages of the disease.